Computational chemistry advances on benzodithiophene-based organic photovoltaic materials. Issue 3 (4th May 2023) - Angel, Felipe A.; Camarada, María B.; Jessop, Ignacio A.
Abstract: Over the past years, highly efficient conjugated polymers and small molecules have led to the development of organic photovoltaics (OPVs) as a promising alternative to conventional solar cells. Among the many designs, benzodithiophene (BDT)-based systems have achieved outstanding power conversion efficiency (PCE), breaking the 10% PCE barrier in the single-junction OPV devices. However, the precise molecular design of BDT-based materials to tune optical and electrochemical properties, morphology, and interaction between layers remains a challenge. At this point, computational chemistry provides an excellent option to supplement traditional characterization methods and, as a vital tool for designing new systems, understanding their structure–property relationship, predicting their performance, and speeding up OPV research. Hence, this review focused on advances in theoretical simulations of BDT-based OPVs during the last decade. First, a brief introduction of theoretical methodologies, including molecular dynamics simulations and quantum-chemical methods, is given. Then, selected examples of BDT-based materials that have shown great potential to generate high-efficiency devices were reviewed, considering DFT, deterministic, and stochastic methods. Finally, prospects and challenges are pointed out for the future design of improved OPVs.